Personality Merchandising and the GDPR: An Insoluble Conflict? - Sun, Jingzhou (Munich Intellectual Property Law Center - MIPLC Studies, 2022)
Upon almost identical conditions of application, the GDPR takes precedence over national legal regime for merchandising. It raises the research question: how would the GDPR regulate merchandising? And, whether the consequences are theoretically justified and practically reasonable? Unlike the GDPR, which is devised to enhance one's control over personal data by omitting its commercial value and limiting personal autonomy in private law, the German legal regime recognizes the pecuniary components in the right to one's image and de facto confirms their licensability. The KUG offers over 100 years of experience in merchandising for the GDPR's risk-based approach.